Islamic Educational Institutions Through Waqf,Maktab, and Kuttab (Correlation of Langghar as a Space for Basic Education) - Khoirina Badriyah (Penerbit Hellow Pustaka, 2025)
Islamic education has a long and rich history marked by the use of various traditional educational institutions such as waqf, maktab, and kuttab. This article explores the role of these institutions in the spread and development of Islamic basic education. Waqf, as a charitable institution managed to support educational activities, has played an important role in financing and providing educational facilities. Maktab, which functions as a basic educational institution that teaches basic Islamic sciences, and kuttab, as an initial educational institution that focuses on teaching the Koran and Arabic, also have significant contributions to the history of Islamic education. This research examines how these three institutions collaborate to support and strengthen Islamic basic education and its impact on society. With historical and contemporary analysis, this article provides insight into how the integration of waqf, maktab, and kuttab has shaped the structure of Islamic education and the challenges and opportunities it faces in the modern context.